POTENCY OF CARBON STORAGE AND CO2 ABSORPTION AT PT TIRTA INVESTAMA, SUBANG DISTRICT - Utami, Widia Sri; Juliani, Rany; Abidin, Zaenal; Santoso, Sidik; Rahayu, Apriliyanti Dwi; Ankhoviyya, Nida (Gorontalo Journal of Forestry Research, 2024)
The Biodiversity Park covering an area of Â±5,800 Ha provides conservation functions in the work area of PT Tirta Investama Plant Subang and for the surrounding community which has a sloping to very steep topography. A landslide disaster occurred in the company's work area in Block II at the beginning of 2024 due to increased rainfall of 17.6 mm/hour caused by global warming. Biodiversity Park also provides the function of reducing greenhouse gas emissions by storing and absorbing CO2 by plants in the area to reduce global warming through photosynthetic activity assisted by energy from sunlight. The research method is to carry out a census inventory of mahogany plants in Block II. This research aims to determine carbon storage and CO2 uptake in mahogany plants. The research show that 412 mahogany plants can store 26,364 tonnes/ha of carbon in their stems or equivalent to an equivalent CO2 uptake of 96,755 tonnes/ha.